Influence of Particle Size of Enogen Feed High Amylase and Conventional Yellow Dent Corn on Lactating Sow Performance - H. R. Williams; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey; S. S. Dritz; C. B. Paulk; H. I. Calderón (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 107 sows (Line; 241 DNA; Columbus, NE) were used in a study to evaluate the effect of Enogen Feed corn and conventional yellow dent corn ground to different particle sizes in lactation diets on sow and litter performance. On d 107 of gestation, sows were blocked by body weight and parity and allotted to 1 of 4 dietary treatments. Dietary treatments consisted of 2 corn sources (Enogen Feed corn and conventional yellow dent) and 2 ground corn particle sizes (600 and 900 microns). A common diet was fed to sows from time of arrival into the farrowing house until they farrowed. Once the sows farrowed, they were fed treatment diets until weaning. Litters were cross fostered across treatments until 48 h post farrowing to equalize litter size. Litters were weighed at birth, d 2, 7, 14, and weaning (d 21). Sow average daily feed intake (ADFI) was measured each time the litters were weighed. There was a tendency for a source × particle size interaction for weight change from farrow to wean (P= 0.065) with the sows fed the 900-micron high amylase corn diets losing less weight compared to sows fed the other diets. From farrow to weaning, there was a corn source × particle size interaction (P= 0.048) for ADFI, with sows fed the conventional corn ground to 900 microns having the lowest ADFI, and sows fed the conventional corn ground to 600 microns having the greatest intake. Litter average daily gain (ADG) and total litter gain tended to be greater (P<0.10) for sows fed diets with 600-micron ground corn compared to the 900-micron ground corn. This is the first study, to our knowledge, that demonstrates the impact of Enogen Feed corn on sow and litter performance. Additional research conducted in a larger scale, commercial facility with more sows is warranted. In summary, there were few differences in sow or litter characteristics among those fed high amylose or conventional yellow dent corn. Sows fed 600-micron ground corn tended to have greater litter ADG and weaning weights, but individual pig weights were not different among treatments.
Keywords: high amylase corn; lactation; particle size; yellow dent corn